Skin Immunity to Dermatophytes: From Experimental Infection Models to Human Disease - Burstein, Verónica L.; Beccacece, Ignacio; Guasconi, Lorena; Mena, Cristian J.; Cervi, Laura; Chiapello, Laura S. (Frontiers in Immunology, 2020)
Dermatophytoses (ringworms) are among the most frequent skin infections and are a highly prevalent cause of human disease worldwide. Despite the incidence of these superficial mycoses in healthy people and the compelling evidence on chronic and deep infections in immunocompromised individuals, the mechanisms controlling dermatophyte invasion in the skin are scarcely known. In the last years, the association between certain primary immunodeficiencies and the susceptibility to severe dermatophytosis as well as the evidence provided by novel experimental models mimicking human disease have significantly contributed to deciphering the basic immunological mechanisms against dermatophytes. In this review, we outline the current knowledge on fungal virulence factors involved in the pathogenesis of dermatophytoses and recent evidence from human infections and experimental models that shed light on the cells and molecules involved in the antifungal cutaneous immune response. The latest highlights emphasize the contribution of C-type lectin receptors signaling and the cellular immune response mediated by IL-17 and IFN-γ in the anti-dermatophytic defense and skin inflammation control